Soil extracellular enzyme activity and stoichiometry in China's forests - Zhou, Luhong; Liu, Shangshi; Shen, Haihua; Zhao, Mengying; Xu, Longchao; Xing, Aijun; Fang, Jingyun; Sayer, Emma (Functional ecology, 2020)
Ecoenzymatic stoichiometry links microbial decomposition with nutrient mineralization and improves our understanding of nutrient cycling in terrestrial ecosystems. Microbial C:N:P acquisition in the topsoil converged at a ratio of 1:1:1 in global ecosystems. However, whether the ratio of microbial acquisition is stable in forest soils, and is applicable among different soil depths remain unknown. Based on large‐scale soil sampling in China's forests, we examined the patterns and environmental drivers of the eight most‐widely measured enzyme activities and the relevant stoichiometry. We found that the ratio of C:N:P acquisition significantly deviated from 1:1:1. The specific enzyme activities (normalized by SOC) did not change significantly with latitude except those for xylosidase and acid phosphatase. Similarly, only the C:P acquisition ratio increased with latitude. Vertically, the specific activities of C‐acquiring enzymes mainly increased, N‐acquiring enzymes decreased and P‐acquiring enzymes did not change with soil depth. Moreover, all ratios of microbial acquisition decreased, and the percentage of recalcitrant C increased significantly with increasing depth. Our study also showed that temperature and soil C:N ratio were the important factors in explaining the variations in specific enzyme activities and microbial nutrient acquisition, respectively. Our results indicated that no constant microbial C:N:P acquisition ratio can be widely recognized, and that SOC quality changed from labile to recalcitrant with depth. We highlight that depth‐dependent enzymatic processes should be considered in future SOC dynamic models. A free Plain Language Summary can be found within the Supporting Information of this article. A free Plain Language Summary can be found within the Supporting Information of this article.